Predictive Effects of Motivation, Attitude, and Gender on Senior Secondary School Students’ Performance in Woodworking Technology - Olabiyi, Oladiran Stephen (INVOTEC, 2021)
The study investigated the predictive effects of motivation, attitudes, and gender on senior secondary year two students’ performance in woodworking technology in Lagos state. It employed the descriptive-correlation method of research and data were obtained using a woodworking proficiency test (WWPT) with a KR-20 reliability coefficient of 0.85 from the sample of 180 students randomly selected. Data were analysed using descriptive and inferential statistics, including mean, standard deviation, independent samples t-test and multiple regression analysis to test hypotheses at 5% level of significance. Findings revealed that motivation and attitude towards woodworking technology predicted students’ performance in woodworking technology. The male students differed from female counterparts in woodworking technology performance. Male students were more motivated and have a positive attitude towards woodworking technology than females. However, no significant difference existed between the mean scores of the male and females in all the variables. It was recommended that educational institutions should have significant influence on students’ motivation and attitude through provision of supportive services, training facilities to engender social creativity and achieving desired goals and meeting required students’ academic performance.